PENDAPATAN USAHA TANI POLA AGROFORESTRI BERBASIS KELAPA (Cocos nucifera) DAN TALAS (Colocasia esculenta L) DI DESA KLABAT, KABUPATEN MINAHASA UTARA - Rahmiyanti Kader; Hengki D. Walangitan; Semuel P. Ratag; Maria Y.M.A. Sumakud (Universitas Sam Ratulangi, 2016)
ABSTRACTCoconut plantation areas in Indonesia, specifically in North Sulawesi by the owners are tendto use monocultural pattern with only one product, copra. Efficiency in using growing spaceand certain planting pattern in form of agroforestry and its combination will give reciprocalbenefits, i.e. the cleanness of coconut planting area could be maintained with a possibility ofincreasing in coconut product, and economical benefits by utilizing of the unused growingspace on the lower space of coconut plantation area. If the economical benefits could bequantified, application of agroforestry pattern could be practiced to a wider area. Applicationof agroforestry pattern between coconut trees (Cocos nucifera) and taro (Colocasia esculentaL) by farmers who work on coconut plantation area is one of the agroforestry pattern that hasbeen used in Klabat Village, North Minahasa Regency. Lacking in knowledge of economicalvalue of the agroforestry pattern applied is a motivation why this reseach was done. Theaimed of this research was to analyze farming revenue based on agroforestry patternapplication between coconut and taro at Klabat Village, North Minahasa Regency.Questionnaire and interview were employed to collect required data and information using 30purposive respondents. This concluded that planting of both crops in combination resulted inhigher revenues than that of monocultural planting.Key words: agroforestry, Klabat village, farming revenue